Critical success factors of supply chain management: An empirical study on a manufacturing company in Malaysia - Thoo, Ai Chin; Huam, Hon Tat; Md Yusoff, Rosman; Rasli, Amran; Abd Hamid, Abu Bakar (2010)
The aim of this study is to shed the light on the critical success factors that lead to high supply chain performance in a manufacturing company. The critical success factors consist of relationships with customer and supplier, information communication and technology (ICT), material flows management, corporate culture and performance measurement. Questionnaire was the main instrument for the study and it was distributed to 84 staffs from departments of purchasing, planning,logistics and operation. Hypotheses were testing by using Statistical Package for Social Science (SPSS) of Windows software. Data analysis was conducted by employing descriptive analysis (mean and standard deviation), reliability analysis, Pearson correlation analysis and multiple regression. The findings show that there are relationships between relationships with customer and supplier, ICT, material flows management, performance measurement and supply chain management (SCM)performance, except for corporate culture. Forming a good customer and supplier relationship is the main predictor of SCM performance, followed by performance measurement, material flows management and ICT. It is recommended that future study to determine additional success factors that are pertinent to firms’ current SCM strategies and directions, competitive advantages and missions. Further study is recommended also to examine a wider scope that includes more geographical data coverage, other nature of businesses and research instruments.